Is there a context-dependent advantage of extra-pair mating in Tree Swallows?. (15th August 2018) - Belmaker, Amos; Hallinger, Kelly K.; Glynn, Rebecca A.; Haussmann, Mark F.; Winkler, David W.
Abstract: The "good-genes" hypothesis to explain female extra-pair mating states that females benefit from this behavior by acquiring better genes for their offspring. Despite extensive research, results are mixed, and the predictions of the good-genes hypothesis have been met in fewer than half of published papers. One possible explanation for this lack of consensus is that the benefits of extra-pair copulation are context-dependent. Here we use chick size, the probability of fledging, and telomeres, the protective caps of chromosomes, as markers for individual quality. Telomere length (TelL) integrates across many stressors and covaries with probability of survival and reproductive success. To test whether benefits to extra-pair (EP) matings are context-dependent we look at the telomere length of extra-pair and within-pair offspring (EPO and WPO, respectively) reared either in experimentally enlarged broods or in broods left at their natural size. We predicted that EPO would have longer telomeres than WPO, and that this difference would be more pronounced among nutritionally limited nestlings reared in enlarged broods. Contrary to our predictions, EP status did not predict chick size or TelL of nestlings reared in either treatment group. EPO from enlarged broods had a higher probability of fledging than similarly reared WPO, but this effect was only seen after a separate analysis per group and not in the full model. Even though these results give mixed support to the good-genes hypothesis they also highlight the difficulty in choosing the proper metric and context.